Study on axial compressive behavior of circular steel tube confined rubberized concrete stub columns. (July 2022) - Zhaoyuan, Yang; Qiyun, Qiao; Wanlin, Cao; Jiafeng, Li
Abstract: An innovative steel tube confined rubberized concrete column is presented in this research to promote waste rubber recycling and improve the mechanical properties of conventional concrete. The axial compressive behavior of circular steel tube confined rubberized concrete (STC-RuC) stub column specimens is experimentally investigated. Thirty-two specimens including twenty-eight STC-RuC specimens and four referenced circular steel tube confined conventional concrete (STCC) column specimens were fabricated and tested. Experimental variables included rubber particle size, volume replacement ratio of the rubber particles, steel tube thickness, and concrete compressive strength. The failure modes, ultimate strength, strain characteristics, rigidity, confinement effect, and ductility were evaluated. The tests showed the failure of the STC-RuC specimens under axial compression was by the core concrete shear failure and the steel tube local buckling. Also, the ultimate strength of STC-RuC specimens was directly proportional to the rubber particle size and steel tube thickness, and it decreased with the increasing volume replacement ratio. With the increasing volume replacement ratio in STC-RuC specimens, the ductility improved, whereas the rigidity decreased. The rigidity increased with the increasing rubber particle size; compared with concrete-filled steel tube (CFST), rubberized concrete-filled steel tube (RuCFST), and STCC stub column specimens, the STC-RuC specimens had better axial compression behavior with a smaller confinement factor. Further, the ultimate strength of STC-RuC specimens was evaluated using various calculation models. The simplified formulae for the prediction of ultimate strengths were also presented.